Les males paraules: insults masculins a la València baixmedieval. - LÓPEZ JUAN, GUILLERMO (Scripta, 2019)
Insults were, during the Middle Ages, more than a way to offend an individual. The ubiquituous culture of honour, which impregnated society and determined men's and women's behaviour, turned them into vituperation, into the public shaming of the insulted person. The responses to these situations were diverse, and depended on the gender, social standing and, ultimately, personal criteria of the slandered individual, but the range of options was broad: retorting with another insult; responding with violence; appealing to the witnesses of the insult; and, finally, denouncing the insulter at the courts of justice. In Valencia, by the end of the 14th century, it seemed that this last resort was particularly frequent, especially among the populace; for this reason, there have been preserved numerous court claims and prosecution records that allow us to observe how verbal violence occurred in the city. In this article, we will analyze insults against men at the end of the 14th century, focusing specially on the slanders more commonly used; the spaces in which verbal disputes took place; and, finally, on the centrality of physical violence as a result, response or companion to verbal offense.